Totem Pro Parte: Narratives of Segunung Traditional Village in Adapting Digital Technology for Tourism - Nuryananda, Praja Firdaus; Berlianty, Evanie Zahra (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
Kampung Adat Segunung, located in Carangwulung village, Jombang, East Java, is an example of a tourism village that applies digitization for tourism development. This can be seen from the intentions and motivations of destination managers who use websites, social media, and the Google Ecosystem in their daily tourism management. This article is a publication of the team's research on the impact of using digital technology in tourism destinations. The research conducted by the research team used a qualitative descriptive method with data collection techniques that relied heavily on interviews, observation results, and literature studies. Managers in Kampung Adat Segunung were also used as research subjects using a participatory rural appraisal approach. Research conducted by the research team found that the positive impact of digital technology adaptation for tourism in the Kampung Adat Segunung still has implications only for destination managers. Most local people are still not positively affected, so they show reluctance to involve themselves in local tourism. In addition, the research team also found that there was an unpreparedness of human resources in terms of their digital capacity to be able to take full advantage of digital technology adaptation. Therefore, the research team concluded that the Kampung Adat Segunung could indeed be an example of a tourist destination in a tourist village that has implemented digital technology for its management. But behind all that, what must also be considered is the readiness of destination managers to make digital technology part of their daily activities and priorities so that the maximum use of digital technology can be made.